2009
DOI: 10.1159/000262320
|View full text |Cite
|
Sign up to set email alerts
|

Successful Uterus-Preserving Surgery for Treatment of Chemotherapy-Resistant Placenta Increta

Abstract: Treatment of placenta increta often entails abdominal total hysterectomy. We present a case of placenta increta in which 3-dimensional computed tomography shows very high blood flow to the placenta, even after chemotherapy with methotrexate. Nonetheless, we were able to remove the region of the uterus that had been invaded by chorionic villi. Massive bleeding during the operation was prevented by ligation of the hypogastric artery and local injection of vasopressin. The combination of chemotherapy and partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Placenta accreta vera is a term used to denote a placenta with villi that adhere to the superficial myometrium; placenta increta occurs when the villi adhere to the body of myometrium, but not through its full thickness; and placenta percreta occurs when the villi penetrate the full thickness of the myometrium. [1][2][3] We demonstrated, by using the FISH technique, that the expression of miR-34a was downregulated in the condition of placenta accreta/increta. In vitro experiments using a choriocarcinoma cell line, JAR, also showed that the invasive potential of JAR cells increased by suppressing the expression of miR-34a, probably through the expression of the plasminogen activator inhibitor-1 (PAI-1).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Placenta accreta vera is a term used to denote a placenta with villi that adhere to the superficial myometrium; placenta increta occurs when the villi adhere to the body of myometrium, but not through its full thickness; and placenta percreta occurs when the villi penetrate the full thickness of the myometrium. [1][2][3] We demonstrated, by using the FISH technique, that the expression of miR-34a was downregulated in the condition of placenta accreta/increta. In vitro experiments using a choriocarcinoma cell line, JAR, also showed that the invasive potential of JAR cells increased by suppressing the expression of miR-34a, probably through the expression of the plasminogen activator inhibitor-1 (PAI-1).…”
Section: Discussionmentioning
confidence: 91%
“…Placenta accreta is generally classified according to its degree of invasion into the myometrium: placenta accreta vera, placenta increta or placenta percreta. Placenta accreta vera is a term used to denote a placenta with villi that adhere to the superficial myometrium; placenta increta occurs when the villi adhere to the body of myometrium, but not through its full thickness; and placenta percreta occurs when the villi penetrate the full thickness of the myometrium 1–3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 53 articles including one prospective cohort study, 2 retrospective cohort studies, 10 case series and 40 case reports with cumulative describing 121 patients [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62]. Our inclusion criteria led to exclusion of 33 patients: 1 patient due to another diagnosis (un-ruptured interstitial corneal pregnancy) [32], 24 patients due to lack of exact reported data [17,51], 4 patients due to initial total hysterectomy [14,17,61], and finally another 4 patients due to other conservative modalities without MTX administration [14,23,42] (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Counseling women requesting uterine conserving treatment of AIP requires knowledge of the evidence regarding the possibility of subsequent pregnancy and associated risk of recurrence of AIP. There are case reports [80][81][82][83][84] (level 4 evidence), case series 49,71,85,86 (level 4 evidence), case-controlled 87 (level 3b evidence) and cohort studies [88][89][90][91][92] This MDT should, as a minimum, include;…”
Section: What Is the Likelihood Of A Further Pregnancy For Women Who mentioning
confidence: 99%